Tingkat Kepatuhan Penggunaan Obat Antituberkulosis pada Pasien Poli Paru di RSU Muhammadiyah Ponorogo - Trilestari (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Compliance with the use of antituberculosis drugs is very important because if treatment is not carried out regularly, it can cause germ resistance, so that adherence to taking medication affects the success of treatment. This study aims to determine the level of adherence to the use of antituberculosis drugs in pulmonary polyclinic patients at RSU Muhammadiyah Ponorogo. This research is a descriptive obsevasional study with a survey design. Sampling was done by purposive sampling method. Data were obtained from the collection of survey results using a questionnaire on pulmonary polyclinic patient at RSU Muhammadiyah Ponorogo. The total population was 115 patients and the samples obtained were 68 patients. Patient compliance data were analyzed and classified into 3 categories, namely high, medium and low adherence. The results showed that the level of adherence to the use of anti tuberculosis drugs at RSU Muhammadiyah Ponorogo had a high category of 58,82%, a medium category of 41,18% and a low category of 0%.